What! Still Alive?! : Jewish Survivors in Poland and Israel Remember Homecoming - Rice, Monika (Book collections on Project MUSE., 2017)
"What! Still Alive?!" offers a powerful and deeply affecting examination of the complex memories of Jewish survivors returning to their homes in Poland after the Holocaust. These survivors left unparalleled testimonies of their first impressions with the Jewish historical commissions from 1944 to 1950. As many survivors found they were no longer welcome by their Polish neighbors, they chose to settle in the new state of Israel. Again, these surviving Jews left testimonies describing their postwar returns. In "What! StillAlive?!," Rice investigates the transformation of survivors' memories from the first account after their initial return to Poland and later accounts, recorded at Yad Vashem in Jerusalem between 1955 and 1970. Through close readings of these firsthand narratives, Rice traces the ways in which the passage of time and a changing geopolitical context influenced the survivors' memories.